Clinical Experience with the Thrombostat 4000 - Alshameeri, Rasheed S; Mammen, Eberhard F (Seminars in Thrombosis and Hemostasis, 1995)
Bleeding times are presently widely used to screen patients with primary hemostasis defects although their accuracy and reliability has been questioned by many investigators. Platelet aggregation studies are not suited for routine use. We investigated the performance characteristics of the Thrombostat 4000, a device that assesses primary hemostasis. Tests can be performed by adding ADP, epinephrine, CaCl2 or NaCl to the collagen onto which platelets adhere. It was found, using normal volunteers and patients, that ADP and epinephrine had acceptable reference ranges with coefficients of variance between 9–12% for within run and between runs. However, major differences were seen when different filter badges were used–a reflection of differences in collagen. Regular citrated blood, routinely drawn for coagulation studies, can be used; test performance can be delayed for up to five hours when the blood is kept at room temperature. The effects of aspirin on volunteers could be detected when epinephrine was used, but not with ADP. ADP addition allowed the detection of more patients with primary hemostasis defects than bleeding times, and epinephrine was as useful as ADP in detecting these abnormalities. The data suggest that the broadest spectrum of platelet defects (ASA use and platelet dysfunction) can be detected with epinephrine. Inconsistencies in collagen used for coating of the filters is a major drawback for the routine use of this device in screening primary hemostasis defects.
Keywords: platelets; primary hemostasis; platelet function; Thrombostat; bleeding time